2017
DOI: 10.1016/j.schres.2016.09.035
|View full text |Cite
|
Sign up to set email alerts
|

The associations between multisensory temporal processing and symptoms of schizophrenia

Abstract: Recent neurobiological accounts of schizophrenia have included an emphasis on changes in sensory processing. These sensory and perceptual deficits can have a cascading effect onto higher-level cognitive processes and clinical symptoms. One form of sensory dysfunction that has been consistently observed in schizophrenia is altered temporal processing. In this study, we investigated temporal processing within and across the auditory and visual modalities in individuals with schizophrenia (SCZ) and age-matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 47 publications
3
93
0
1
Order By: Relevance
“…The CognitivePerceptual component concerns the disposition to unusual perceptual experiences, such as hallucinations, which are associated with impaired multisensory integration and TBW in patients. 7,79 Hence, we specifically focused on this subscale in our analysis. While its distribution was slightly positively skewed, its skewness and kurtosis were within the acceptable range (skewness < 1, kurtosis < 2.5).…”
Section: Schizotypal Personality Questionnairementioning
confidence: 99%
“…The CognitivePerceptual component concerns the disposition to unusual perceptual experiences, such as hallucinations, which are associated with impaired multisensory integration and TBW in patients. 7,79 Hence, we specifically focused on this subscale in our analysis. While its distribution was slightly positively skewed, its skewness and kurtosis were within the acceptable range (skewness < 1, kurtosis < 2.5).…”
Section: Schizotypal Personality Questionnairementioning
confidence: 99%
“…In addition to findings of unisensory processing deficits, there is also some evidence for aberrant multisensory processing in SCZ (Foucher et al, 2007; Stekelenburg et al, 2013; Roa Romero et al, 2016a,b; Stevenson et al, 2016; for a review see Tseng et al, 2015). One study examined simultaneity judgments in unisensory and multisensory stimuli and found that SCZ have a lengthened window of simultaneity for unisensory visual, unisensory auditory, and bisensory audiovisual stimuli (Foucher et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One possible way this could be done is through dynamically changing the timing over which stimuli are bound and integrated (i.e., an alteration in the size of temporal-binding windows, TBW; Stevenson et al 2016; Noel et al 2015a, 2016a, b, 2017a, b; De Niear et al 2017). Alternatively, compensation for the changing spatiotemporal characteristics of the stimuli may be accomplished by shifting the temporal asynchrony that is considered most synchronous (i.e., an alteration in the point of subjective simultaneity, PSS).…”
Section: Introductionmentioning
confidence: 99%